2007
DOI: 10.1667/rr0969.1
|View full text |Cite
|
Sign up to set email alerts
|

The Characterization and Transmissibility of Chromosome Aberrations Induced in Peripheral Blood Lymphocytes byIn Vitroα-Particle Radiation

Abstract: Peripheral blood lymphocytes were irradiated in vitro with (213)Bi alpha particles at doses of 0, 10, 20, 50, 100, 200 and 500 mGy. Chromosome analysis was performed on 47-h cultures using single-color fluorescence in situ hybridization (FISH) to paint chromosomes 1, 3 and 5. The whole genome was analyzed for unstable aberrations to derive aberration frequencies and determine cell stability. The dose response for dicentrics was 33.60 +/- 0.47 x 10(-2) per Gy. A more detailed analysis revealed that the majority… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…This is an established aberration profile for cumulative in vivo external low dose, low dose rate, cumulative c-ray exposure as radiation-induced aberrant cells will usually contain just one single simple aberration (Tawn et al, in preparation). In vitro studies have demonstrated that the most likely outcome of a single nuclear traversal by an aparticle is a complex aberration involving multiple breaks in multiple chromosomes (Anderson et al 2002(Anderson et al , 2005Tawn et al 2007;Curwen et al 2012). However, the vast majority of the cells containing such damage will be unstable and eliminated during subsequent cell divisions, and it is the cells with the less frequently induced simple translocations that survive.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is an established aberration profile for cumulative in vivo external low dose, low dose rate, cumulative c-ray exposure as radiation-induced aberrant cells will usually contain just one single simple aberration (Tawn et al, in preparation). In vitro studies have demonstrated that the most likely outcome of a single nuclear traversal by an aparticle is a complex aberration involving multiple breaks in multiple chromosomes (Anderson et al 2002(Anderson et al , 2005Tawn et al 2007;Curwen et al 2012). However, the vast majority of the cells containing such damage will be unstable and eliminated during subsequent cell divisions, and it is the cells with the less frequently induced simple translocations that survive.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies on the induction of chromosome aberrations by a-particle radiation have revealed the complexity of the damage (Anderson et al 2000;Moquet et al 2001;Anderson et al 2002Anderson et al , 2003Barquinero et al 2004;Anderson et al 2007;Tawn et al 2007Tawn et al , 2008Curwen et al 2012). A densely ionizing a-particle will only intersect a small fraction of the cell volume and the deposition of energy and resulting DNA damage will be localized along the particle track, resulting in multiple rearrangements.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The low viability of human lymphocytes that contain complex aberrations has been shown experimentally by Anderson et al (2003). Tawn et al (2007) recently found that the RBE for induction of stable translocations by exposure to 213 Bi alpha particles, relative to the doselinear term of low-LET gamma rays, was only three, whereas the RBE for initial induction of dicentrics was 14. The low probability for hemopoietic cells, including stem cells, to survive the passage of a single alpha particle (Lorimore et al 1993;Griffiths et al 1994) may be the main explanation for the observed RBE for human leukemia apparently being much lower than the w R of 20 specified for alpha particles in radiation protection.…”
Section: Are Dose Responses For Dicentric Aberrations Under Various Ementioning
confidence: 88%